Off-line tetramethylammonium hydroxide thermochemolysis of model compound aliphatic and aromatic carboxylic acids: Decarboxylation of some ortho- and/or para- substituted aromatic carboxylic acids - Joll, Cynthia; Huynh, Tran; Heitz, Anna (Elsevier, 2003)
Tetramethylammonium hydroxide (TMAH) thermochemolysis was performed 'off-line' on a wide variety of aliphatic and aromatic carboxylic acids, as model compounds for moieties present in polymeric organic materials. Simple aliphatic carboxylic acids and some aromatic carboxylic acids afforded only products of full or partial methylation. Aromatic carboxylic acids with ortho and/or para substituents which contain an unshared pair of electrons on the atom connected to the ring and which are activating to electrophilic aromatic substitution (e.g. phenoxide, hydroxy, methoxy, amino) exhibited varying degrees of decarboxylation under standard reaction conditions. Detailed reaction mechanisms to explain the formation of all key products are presented in this paper. The extent of the decarboxylation was found to be dependent upon the mole ratio of TMAH to which the model compound was exposed: a reduction in the mole ratio of TMAH to model compound reducing or eliminating the formation of decarboxylation products. These results indicate that interpretation of product mixtures from TMAH thermochemolysis of polymeric organic matter, in particular the heterogeneous humic substances, must be made with caution and the origins of hydroxy- and methoxy-benzene products must be considered to include hydroxy- and methoxy-benzoic acids.